Immunological indices of Giant African Land snails (Archachatina marginata) improved with fixed dose of vitamin C during acute heat stress - Iwuozo, Odinaka Christian; Abiona, John Adesanya; Abioja, Monsuru Oladimeji; Ilori, Babatunde Moses (Acta Scientiarum. Animal Sciences, 2022)
The study determined immunological indices of Giant African Land snail (Archachatina marginata) improved with fixed dose of vitamin C under acute heat stress (AHS). Prior to the AHS, vitamin C was administered for four weeks to two treatment groups, while other two treatment groups were not. Each treatment was monitored, haemolymph collected at 0, 30 and 60 minutes exposure times. Immunological cytokines: interferon gamma (IFN-γ) and interleukin 2 (IL-2); and total haemocyte counts (THC) were determined. Under AHS, vitamin C elevated (p <0.05) IFN-γ production (606.33 ± 302.86) compared to other groups with or without vitamin C administration (7.20 ± 1.58 vs. 73.20 ± 32.23 vs. 7.80 ± 1.36). IL-2 was not affected (p >0.05) by vitamin C under AHS. Highest (p <0.05) THC values was obtained with vitamin C administration under AHS, but reduced under no AHS. Exposure time affected (p <0.05) IFN-γ production and THC values, but not IL-2 (p >0.05). With fixed dose of vitamin C and exposure time, highest (p <0.05) IFN-γ values were obtained under AHS with vitamin C administration at 30 minutes and at 60 minutes in THC, compared to other groups. The study concluded that fixed dose of vitamin C at 150 mg kg-1 of feed was appropriate under AHS to boost the immune system of the animals.